2015
DOI: 10.3892/etm.2015.2385
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas inhalation protects against liver ischemia/reperfusion injury by activating the NF-κB signaling pathway

Abstract: Abstract. Hydrogen has been demonstrated to function as a novel antioxidant and exert therapeutic antioxidant activity in a number of diseases. The present study was designed to investigate the effect of hydrogen inhalation on liver ischemia/reperfusion (I/R) injury in rats. The portal triad to the left lobe and the left middle lobe of the liver were completely occluded for 90 min. This was followed by reperfusion for 180 min. The rats subsequently underwent syngeneic orthotopic liver transplantation. Inhalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Hydrogen therapy is protective against ischemic injury across a range of organs when administered as a gas or enriched solution (6)(7)(8)15). It is able to permeate the cellular wall and diffuse into the cytosol, mitochondria, and nucleus reducing hydroxyl radicals without affecting oxidation reduction reactions or levels of H 2 O 2 and NO (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen therapy is protective against ischemic injury across a range of organs when administered as a gas or enriched solution (6)(7)(8)15). It is able to permeate the cellular wall and diffuse into the cytosol, mitochondria, and nucleus reducing hydroxyl radicals without affecting oxidation reduction reactions or levels of H 2 O 2 and NO (4).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen has demonstrated a beneficial effect in all solid organs. Several rodent models have shown a beneficial effect in reducing acute and chronic transplant doi: 10.1111/aor.13118 related ischemic injury (6)(7)(8)(9)(10)(11)(12)(13). Nonetheless, there are few clinically relevant studies examining the effect of hydrogen on acute renal function and ischemia reperfusion injury (IRI).…”
mentioning
confidence: 99%
“…In 1975, Dole and colleagues reported in Science that hyperbaric hydrogen therapy (2.5% oxygen and 97.5% hydrogen under 8-atmospheric pressure) reduced the size of the squamous cell carcinoma tumors in hairless mice 45 . In 2007, Ohsawa and colleagues published a report in Nature Medicine that showed that inhalation of 1–4% hydrogen gas markedly reduced the size of cerebral infarction in rats, which ignited interest in the biomedical effect of molecular hydrogen in various diseases 46 , 47 . A large number of studies have reported that molecular hydrogen has significant protective effects on many neurological diseases, including neuropathic pain, cerebral injury, Alzheimer’s Disease, Parkinson’s Disease and so on 48 – 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the hydrogen molecule is electrically neutral and considerably smaller than other antioxidants, it can easily penetrate membranes and enter organelles (12,26); however, it remains unclear exactly what type of oxidative stress is involved in femoral head necrosis. GSH stabilizes the lysosomal membranes to suppress injury to the vascular endothelium.…”
Section: A B a B Discussionmentioning
confidence: 99%